2020
DOI: 10.3390/ani10071209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inclusion of Different Doses of Persicaria odorata Leaf Meal (POLM) in Broiler Chicken Feed on Biochemical and Haematological Blood Indicators and Liver Histomorphological Changes

Abstract: This research was conducted to estimate the effects of Persicaria odorata leaf meal (POLM) on haematological indices, serum biochemical attributes, and internal organs parameters, including histomorphological features of the liver, in broiler chickens. A total of 120 one-day-old male broiler chicks (Cobb-500) were randomly allocated into four experimental groups. The dietary treatments were basal diet (BD), which served as the control (C), along with BD + 2 g/kg POLM (Po2), BD + 4 g/kg POLM (Po4), BD + 8 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
(93 reference statements)
3
11
0
Order By: Relevance
“…In terms of the cholesterol content, all animal groups differed, and, with the exception of the groups CPFA 2 and CPFA 4, were higher than in the control ( p > 0.05). The data obtained by us are consistent with the data of Basit et al (2020) [ 66 ], whose study showed that on the 21st day of the supplement, flour from Persicaria odorata leaves did not affect the content of triglycerides and cholesterol in blood serum on the 21st day of cultivation. Opposite results were obtained by Vispute et al (2019) [ 21 ], who reported that dill and hemp seeds significantly reduce serum triglyceride levels during the growth phase.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the cholesterol content, all animal groups differed, and, with the exception of the groups CPFA 2 and CPFA 4, were higher than in the control ( p > 0.05). The data obtained by us are consistent with the data of Basit et al (2020) [ 66 ], whose study showed that on the 21st day of the supplement, flour from Persicaria odorata leaves did not affect the content of triglycerides and cholesterol in blood serum on the 21st day of cultivation. Opposite results were obtained by Vispute et al (2019) [ 21 ], who reported that dill and hemp seeds significantly reduce serum triglyceride levels during the growth phase.…”
Section: Discussionsupporting
confidence: 92%
“…The broiler chickens in all groups were reared under the same environmental and managemental conditions. The cyclic temperature in the house ranged between a maximum of 34 • C and a minimum of 24 • C, while the humidity ranged between a maximum of 91% and a minimum of 65% [34]. This study consisted of five dietary groups, and the diets were offered to the birds for 42 days (starter phase day 1-21 and finisher phase day .…”
Section: Experimental Design and Supplemented Dietsmentioning
confidence: 99%
“…The supplemented diets were the basal diet (BD), which served as the negative control (NC); BD + 0.2 g/kg tetracycline, which served as the positive control (PC); BD + 0.03 g/kg halquinol (HAL), BD + 8 g/kg POLM (Po8), and BD + 4 g/kg PBLM (Pb4), which were the treatment groups. The specific concentrations of diets were selected as earlier reported, PC [47], Po8 and Pb4 [16,34], while HAL as designated by [44]. There was free access to water and feed to the chicks during the entire experimental period, with continuous lighting.…”
Section: Experimental Design and Supplemented Dietsmentioning
confidence: 99%
See 2 more Smart Citations